Clinical withdrawal symptom profile of synthetic cannabinoid receptor agonists and comparison of effects with high potency cannabis - Sam Craft; Jason A. Ferris; Monica J. Barratt; Larissa J. Maier; Michael T. Lynskey; Adam R. Winstock; Tom P. Freeman (Psychopharmacology, 2022)
Synthetic cannabinoid receptor agonists (SCRAs) may be used as an alternative to natural cannabis; however, they may carry a greater risk of problematic use and withdrawal. This study aimed to characterise the withdrawal symptom profile of SCRAs and compare their profile of effect with high-potency herbal cannabis. Global Drug Survey data (2015 and 2016) were used to access a clinically relevant sample of people reporting use of SCRAs >10 times in the past 12-months, a previous SCRA quit attempt, and lifetime use of high-potency herbal cannabis. Participants completed an 11-item SCRA withdrawal symptom checklist and compared SCRAs and high-potency herbal cannabis on their onset and duration of effects, speed of the development of tolerance, severity of withdrawal, and difficulty with dose titration. Participants ( n = 284) reported experiencing a mean of 4.4 (95% CI: 4.1, 4.8) withdrawal symptoms after not using SCRAs for >1 day; most frequently reported were sleep issues (59.2%), irritability (55.6%), and low mood (54.2%). Withdrawal symptoms were significantly associated with frequency (>51 vs. 11–50 times per year: IRR = 1.43, 95% CI: 1.16, 1.77, p = 0.005) and quantity (grams per session: IRR = 1.13, 95% CI: 1.05, 1.22, p = 0.001) of SCRA use. Compared to high-potency herbal cannabis, SCRAs were rated as having a faster onset and shorter duration of effects, faster development of tolerance, and more severe withdrawal ( p ’s < 0.001). In conclusion, SCRA withdrawal symptoms are more likely to occur after greater SCRA exposure. The effects of SCRA indicate a more severe withdrawal syndrome and a greater risk of problematic use than natural cannabis.

Oceans Across the Solar System and the Search for Extraoceanic Life: Technologies for Remote Sensing and In Situ Exploration - Ved Chirayath; Elizabeth Bagshaw; Kate Craft; Heidi Heidi; Darlene Lim; Michael Malaska; Oscar Pizarro; Sam Purkis; Dustin Schroeder; Pablo Sobron; Sarah Waller; Dale Winebrenner (Oceanography, 2022)
Earth’s ocean comprises 99% of the habitable volume of our planet and contains the largest biomass and species diversity in the known universe. Perhaps unsurprisingly, recent advances in the search for life elsewhere in our solar system have increasingly pointed to potentially viable niches for life on other dynamic ocean worlds such as Titan, Europa, and Enceladus, among other moons of the outer gas giants. Indeed, the discovery of extraterrestrial life on these icy water bodies may motivate adopting an altogether new terminology and further non-anthropic perspective on the cosmos for what may well prove to be an abundant and diverse extraoceanic life, to coin a term. Exploration of such ocean worlds across the solar system will undoubtedly be enabled by technological developments in a range of sensing methodologies primarily developed for oceanography on Earth. As we have learned studying our home ocean, where less than 10% of the benthic surface has been optically imaged, the challenge is daunting, yet recent advances give hope. Here, we review some of the state-of-the-art techniques from oceanography and planetary science that may inform sensing of the biological and geophysical properties of ocean worlds, ranging from large-scale synoptic views afforded by active and passive remote sensing to in situ autonomous sampling and methods for detecting biosignatures.